Efficiency and Effectiveness of Disclosure of Cooperation with Online - Indo Yama Nasaruddin (Esensi: Jurnal Bisnis dan Manajemen, 2020)
This research measures the efficiency and effectiveness of the dissolution of cooperatives conducted online. To see the efficiency and effectiveness of using cooperative dissolution performance variables, utilization of online services, performance in online services and interest in utilizing online services for cooperatives in cooperative dissolution activities. The analysis technique used is descriptive analysis by looking at the percentage of answers from respondents. The object of this research is cooperatives that are listed as cooperatives which are dissolved in the area of East Java Province and Yogyakarta Special Region as regions that have many cooperative dissolutions. The results showed that the performance of the dissolution of cooperatives in the Special Region of Yogyakarta and East Java Province was an average of 3.53 in the predicate of moderate capacity. Utilization of online services is quite high. The performance of online services obtained the average results of respondents' answers of 4.09 are in the predicate of high capacity. Interest in the need for cooperative online services as an alternative to cooperative dissolution systems in the Special Region of Yogyakarta and East Java Province is high.